Health and economic impact at a population level of both primary and secondary preventive lung cancer interventions: A model-based cost-effectiveness analysis. (September 2021) - Diaz, Mireia; Garcia, Montse; Vidal, Carmen; Santiago, Albert; Gnutti, Gerard; Gómez, David; Trapero-Bertran, Marta; Fu, Marcela; ,
Highlights: Quitting interventions are more effective and cost-effective at younger ages. Integration of quitting interventions into LDCT screening is highly effective. Combined strategies are more cost-effective than both approaches separately. Both interventions should be considered as complementary strategies. Findings could be generalizable to other industrialized countries. Abstract: Objectives: Robust economic evaluations are needed to identify efficient strategies for lung cancer prevention that combine brief and intensive smoking cessation intervention programmes with screening using low-dose computed tomography (LDCT) at different ages, frequencies, and coverages. We aimed to assess the cost-effectiveness of smoking cessation approaches combined with lung cancer screening in the European context at a population level from a societal perspective. Materials and Methods: A microsimulation model that describes the natural history of lung cancer and incorporates several prevention strategies was developed. Discounted lifetime QALYs and costs at a rate of 3% were used to calculate incremental cost-effectiveness ratios, defined as additional costs in 2017 Euros per QALY gained. Results: Smoking cessation interventions reduce the incidence of lung cancer by 8%-46% and are consistently more effective and cost-effective when starting at younger ages. Screening reduces lung cancer mortality by 1%-24% and is generally less effective and more costly than smoking cessation interventions. The most cost-effective strategy would be to implement intensive smoking cessation interventions at ages 35, 40 and 45, combined with screening every three years between the ages of 55 and 65. Conclusions: Combining smoking cessation interventions with LDCT screening is a very attractive prevention strategy that substantially diminishes the burden of lung cancer. These combined prevention strategies, especially when providing several intensive interventions for smoking cessation at early ages, are more cost-effective than both approaches separately and allow for a more intensified LDCT without losing efficiency.